2014
DOI: 10.1038/bjc.2014.356
|View full text |Cite
|
Sign up to set email alerts
|

A phase IIa dose-finding and safety study of first-line pertuzumab in combination with trastuzumab, capecitabine and cisplatin in patients with HER2-positive advanced gastric cancer

Abstract: Background:Pertuzumab plus trastuzumab provides a more comprehensive blockade of HER2 signalling than trastuzumab alone. Therefore, we conducted a phase IIa study of the pharmacokinetics and safety of pertuzumab plus trastuzumab and chemotherapy in advanced gastric cancer (aGC).Methods:Patients received pertuzumab 840 mg for cycle 1 and 420 mg q3w for cycles 2–6 (Arm A) or pertuzumab 840 mg q3w for six cycles (Arm B). Trastuzumab, cisplatin and capecitabine were also given for six cycles, then trastuzumab q3w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 45 publications
4
50
0
2
Order By: Relevance
“…In addition, no cases of cardiac failure or mortality due to cardiac toxicity were observed. Similarly, previous reports have shown that adding trastuzumab to chemotherapy does not increase the toxic effects associated with standard fluoropyrimidine and platinum chemotherapy (4,(16)(17)(18)(19). The toxicity profile of trastuzumab plus chemotherapy has been shown to be comparable to that for chemotherapy alone in phase II and III trials (4,20,21).…”
Section: No Patients -----------------------------------------------mentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, no cases of cardiac failure or mortality due to cardiac toxicity were observed. Similarly, previous reports have shown that adding trastuzumab to chemotherapy does not increase the toxic effects associated with standard fluoropyrimidine and platinum chemotherapy (4,(16)(17)(18)(19). The toxicity profile of trastuzumab plus chemotherapy has been shown to be comparable to that for chemotherapy alone in phase II and III trials (4,20,21).…”
Section: No Patients -----------------------------------------------mentioning
confidence: 56%
“…High efficacy of trastuzumab has been confirmed prior to and following chemotherapy in patients with HER2-positive breast cancer, and expanded indications in gastric cancer are anticipated (14,15). Previous studies that have assessed chemotherapy plus trastuzumab treatment regimens for patients with HER2-positive gastric cancer have revealed good tolerance and high efficacy with cytotoxic chemotherapy including S-1 plus cisplatin, capecitabine plus oxaliplatin (or docetaxel), and cisplatin plus S-1, however, not capecitabine plus cisplatin (16)(17)(18)(19)(20)(21). Therefore, trastuzumab with cytotoxic chemotherapy is considered a standard treatment regimen for patients with HER2-positive gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recurrent amplification of genes associated with the receptor tyrosine kinase pathway, such as EGFR, ERBB2, ERBB3, JAK2, FGFR2, and MET, and the angiogenesis pathway, such as VEGFA, have been reported in GC [4,5]. With the exception of a subset of patients with ERBB2 amplification who experienced benefits from trastuzumab [6], targeted agents for aberrant gene amplification have not yet been successful in therapeutic applications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The administration of pertuzumab is approved for metastatic breast cancer [31] . The combination of pertuzumab and trastuzumab seems to be effective in advanced gastric cancer with overall response rates up to 86% [32] .…”
Section: Growth Factors Growth Factor Receptors and Downstream Featuresmentioning
confidence: 99%